RHENIUM IN ORES OF PORPHYRY COPPER DEPOSITS IN THE URALS - Grabezhev A.I. (My University, 2007)
The geochemistry of rhenium in ores of porphyry copper deposits, which serve as the major industrial source of this element, has been discussed in numerous publications. However, data on the Re distribution in ores are lacking for deposits in the Urals. It is known that the majority of porphyry copper deposits in the Urals formed in an island-arc setting associated with minor plagiogranitoid intrusions (hereafter, plutons) of elevated basicity. Such conditions are considered very favorable for the accumulation of Re in ores. The present paper is devoted to the concentration of Re in deposits of various geotectonic settings in the central and southern Urals. The Re–Mo relationship is discussed with consideration of the close geochemical correlations between these elements.